2013
DOI: 10.1186/1471-2229-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance, Na+ exclusion and allele mining of HKT1;5 in Oryza sativa and O. glaberrima: many sources, many genes, one mechanism?

Abstract: BackgroundCultivated rice species (Oryza sativa L. and O. glaberrima Steud.) are generally considered among the crop species most sensitive to salt stress. A handful of lines are known to be tolerant, and a small number of these have been used extensively as donors in breeding programs. However, these donors use many of the same genes and physiological mechanisms to confer tolerance. Little information is available on the diversity of mechanisms used by these species to cope with salt stress, and there is a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
209
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 53 publications
9
209
1
Order By: Relevance
“…LEA proteins are mainly low-molecular-weight (10-30 kDa) proteins involved in protecting higher plants from damage caused by environmental stresses, especially drought or dehydration [42][43][44][45]. HKT transporters mediate Na C unloading from the xylem under salinity stress, which prevents Na C overaccumulation in leaves, thereby protecting photosynthetic organs [46][47][48][49]. It is, therefore, tempting to speculate that the overexpression of OsDUF946.4 might have resulted in upregulated expression of LEA protein-like and HKT-transporter-like genes in E. coli, which could have led to the enhanced tolerance to drought and salinity.…”
Section: Expression Analysis Of Osduf946 Genes Under Various Stress Cmentioning
confidence: 99%
“…LEA proteins are mainly low-molecular-weight (10-30 kDa) proteins involved in protecting higher plants from damage caused by environmental stresses, especially drought or dehydration [42][43][44][45]. HKT transporters mediate Na C unloading from the xylem under salinity stress, which prevents Na C overaccumulation in leaves, thereby protecting photosynthetic organs [46][47][48][49]. It is, therefore, tempting to speculate that the overexpression of OsDUF946.4 might have resulted in upregulated expression of LEA protein-like and HKT-transporter-like genes in E. coli, which could have led to the enhanced tolerance to drought and salinity.…”
Section: Expression Analysis Of Osduf946 Genes Under Various Stress Cmentioning
confidence: 99%
“…The Na+ and K+ content in shoots and roots were measured using a capillary electrophoresis system (Capel-105M; Lumex, Russia) according to the method of Platten et al (2013).…”
Section: Determining Concentrations Of Sodium and Potassiummentioning
confidence: 99%
“…Presently, a major QTL SalTol associated with the Na-K ratio in rice and seedlingstage salinity tolerance, are marked on chromosome 1 (Platten et al, 2013). Nevertheless, allelic variations of microsatellite loci associated with specific trait in related groups of genotypes do not always correlate with that trait in genotypes other origins (Senadheera et al, 2009;Mardani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awala et al (2010) reported that O. glaberrima CG14 appeared rather salt-sensitive but the obtained hybrids after crossing this line with the O. sativa WAB56-104 cultivar produced hybrids exhibiting a high level of salinity resistance. Platten et al (2013) quantified Na + accumulation in several salt-exposed lines of O. glaberrima and identified a specific gene (OgHKT1;5) which partly contribute to regulate Na + absorption and translocation.…”
Section: Introductionmentioning
confidence: 99%